Memaknai Transparansi Internet Financial Reporting Lembaga Amil Zakat Melalui Konsep Amanah dan Tablig - Nur Amalia Aziza; Nur Afiani (Jurnal Akuntansi dan Governance, 2023)
The limited transparency of amil zakat institutions, especially on financial aspect, has an impact on public trust and their ability to survive considering all funds come from the public. The purpose of this study is to reveal the meaning of transparency through online financial reporting based on the concept of trust and tabligh. Being in a religious interpretive paradigm, this study employs qualitative approach. Data collection was carried out by interviewing managers and from archives of published financial reports on the LAZ Dompet Dhuafa Republika website. The results show that transparency is interpreted as the principle of responsibility in overcoming transparency obstacles, transparent content as institutional morality, and media transparency as institutional attachment which should be carried out continuously